Tinjauan Kritis terhadap Metode Tafsir Maudhu’i - Ihsan Nursidik; Muhammad Erpian Maulana (Jurnal Iman dan Spiritualitas, 2021)
The interpretation of the Qur'an is a scientific activity in the scientific family of usuluddin or covers the central affairs of the Islamic religion. The existence of this science is so important because without it the Qur'an cannot be understood clearly. Especially considering the context of the times that continue to develop and change. This reality encourages scholars, commentators, and reviewers of the Qur'an to create new methodologies in interpreting the Qur'an. Maudu'i's interpretation is one of the scientific products. This Tafsir method is part of the scientific development of Tafsir in the contemporary era. However, this does not mean that its new presence will outperform other interpretation methods, of course, as a scientific methodology, there will always be advantages and disadvantages. This study aims to reveal Tafsir Maudu'i and its advantages and disadvantages as one of the Quranic research methodologies related to it as a methodology. This research shows that Tafsir maudu'i has elementary things, which are the keys that distinguish the Tafsir Maudu'i method from other methods. Then another thing is regarding the advantages and disadvantages of this interpretation which can be seen from the relation that uses tartib al-nuzul in the way it is presented.